Hybrid identities: juxtaposing multiple identities against the 'authentic' Moken. Issue 5 (2nd September 2016) - Robinson, Daniel F.; Drozdzewski, Danielle
Abstract : The Moken and Moklen are an indigenous population residing along the Andaman coast of Thailand. They have been represented, both in popular and academic discourse, as seafaring nomads living in traditional boats and small temporal coastal communities. The overwhelmingly precept of the existing literature about the Moken is one of vulnerability and of stemming the erosion of 'authentic' Moken cultural identities. Identification of Moken as being under threat transpired as a consequence of the 2004 Asian tsunami, in which many Moken were killed and the plight of others who had their houses and sources of livelihood destroyed was propelled onto an international stage. This paper critically discusses how Moken identities and associated discourses of vulnerability have been depicted in media and academic literature as fixed and traditional. We argue that such rigid identity narratives contrast sharply to the contemporary realities of the Moken identities as articulated by the Moken we interviewed.